Small-Scale Energy Harvesting - Lallart, Mickael (IntechOpen, 2012)
The purpose of this book is to provide an up-to-date view of latest research advances in the design of efficient small-scale energy harvesters through contributions of internationally recognized researchers. The book covers the physics of the energy conversion, the elaboration of electroactive materials and their application to the conception of a complete microgenerator, and is organized according to the input energy source. I sincerely hope you will find this book as enjoyable to read as it was to edit, and that it will help your research and/or give new ideas in the wide field of energy harvesting.